ASEAN in the Middle of US and Chinese Rivalry: ASEAN Cooperation with RCEP in Reducing the Impact of the Trade War - Haren Ke (International Journal of Science and Society, 2019)
Competition between the US and China over trade wars has a significant impact on many countries in the world, including ASEAN. The ASEAN region is a central market in the Pacific. Because of this competition, each Chinese export to the US will decrease by around 10%, and also reduce economic growth by 1.1% in ASEAN. This phenomenon raises significant questions about the role of ASEAN. This research paper will answer the purpose of ASEAN as a multilateral organization in balancing its interests amid a trade war. After that, this paper focuses on the topic of competition between the US and China related to the economy. This discussion is divided into two main points, first is about the trade war, and the second is the role of RCEP to build ASEAN economic balance. International cooperation on a liberal perspective is used to analyze the problems in this case. This paper argues that ASEAN seeks to encourage collaboration between its members to face the challenges of the US and China trade wars. Cooperation is the best way for ASEAN to see this phenomenon.